POTENTIAL ROLES OF BIOTIC FACTORS IN REGULATING ZOOPLANKTON COMMUNITY DYNAMICS IN JAKARTA BAY SHALLOW WATER COASTAL ECOSYSTEM - Arief Rachman; Nurul Fitriya (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
The dynamics in zooplankton abundance were regulated by changes in water physical-chemical parameters and interaction with biotic factors. In this research we examined the relationship between zooplankton community dynamic and important biotic factors, such as predation and food availability, in Jakarta bay. Plankton samplings were done in 10 sampling stations in Jakarta bay, from July to November 2009. Zooplankton samples were collected using horizontal towing method with NORPAC plankton net (mesh size 300 μm). Salinity, water depth, water temperature, and water transparency were measured. Phytoplankton samples were also collected with the same method as zooplankton, using Kitahara plankton net (mesh size 80 μm). Zooplankton taxas were grouped into two groups, the prey and predatory zooplankton. The results showed that there were two different patterns in zooplankton groups dynamic i.e., the single and double peak. The abundance peak in most zooplankton groups, such as copepods, cirripeds, luciferids, and tunicates, were induced by the high food availability during the phytoplankton bloom in August. The high abundance of prey zooplankton groups in August was responded by the predatory zooplankton groups, resulting in high abundance of predatory zooplankton in adjacent month. The high abundance of ctenophores and chordates (fish larvae) were suggested as the main factor for the low abundance of other zooplankton in September. Physical and chemical factors were not the regulating factors due to the stability of those factors during this research period. Thus we concluded that food availability and predator-prey interaction were the main factors which regulate zooplankton community dynamics in Jakarta bay.Keywords: predator-prey interaction, zooplankton, abundance peak, food availability, phytoplankton bloom